2015
DOI: 10.18632/oncotarget.5955
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade attenuates immunosuppressive myeloid cells due to inhibition of CD47/SIRPα axis in HPV negative head and neck squamous cell carcinoma

Abstract: Myeloid-derived suppressor cells (MDSCs) and tumor associated macrophages (TAMs) play key roles in the tumor immune suppressive network and tumor progression. However, precise roles of programmed death-1 (PD-1) in immunological functions of MDSCs and TAMs in head and neck squamous cell carcinoma (HNSCC) have not been clearly elucidated. In the present study, we show that PD-1 and PD-L1 levels were significantly higher in human HNSCC specimen than in normal oral mucosa. MDSCs and TAMs were characterized in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 56 publications
3
102
0
Order By: Relevance
“…More difficult to explain is the underlying cause for the more rapid decay in this immune activity in mice receiving PD‐1 antibody treatment compared to the mice receiving control treatment. It is important to note that, in the HNSCC environment, there are multiple mechanisms contributing to the immune dysfunction including inhibitory mediators such and PGE 2 produced directly by the tumor cells as well as tumor‐induced immune inhibitory cells such as Treg, MDSC and the less mature CD34 + progenitor cells, infiltrating macrophages and endothelial cells 10, 11, 12, 13, 14. Studies have not, however, been conducted to determine at what point and in what sequence during progression of premalignant oral lesions to HNSCC these various inhibitory mediators and cells overcome the immune defenses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More difficult to explain is the underlying cause for the more rapid decay in this immune activity in mice receiving PD‐1 antibody treatment compared to the mice receiving control treatment. It is important to note that, in the HNSCC environment, there are multiple mechanisms contributing to the immune dysfunction including inhibitory mediators such and PGE 2 produced directly by the tumor cells as well as tumor‐induced immune inhibitory cells such as Treg, MDSC and the less mature CD34 + progenitor cells, infiltrating macrophages and endothelial cells 10, 11, 12, 13, 14. Studies have not, however, been conducted to determine at what point and in what sequence during progression of premalignant oral lesions to HNSCC these various inhibitory mediators and cells overcome the immune defenses.…”
Section: Discussionmentioning
confidence: 99%
“…These include tumor production of immune inhibitory mediators and tumor induction of host immune suppressor cells. Among the immune suppressive cells induced by HNSCC are Treg, inhibitory tumor‐associated macrophages and fibroblasts, myeloid‐derived suppressor cells (MDSC) and the less mature CD34 + progenitor cells 10, 11, 12, 13, 14. More recently, attention has focused on mechanisms involving activation of immune checkpoint signaling such as through PD‐1 ligand and its PD‐1 receptor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A constant exposure with tumor antigen increases the activity of PD-1 on the surface of T cells which eventually generates a population of exhausted and abnormal T cells with aberrant signals to fight cancer cells. More recently, Sun and colleagues demonstrated that PD-1 overexpression is a general phenomenon irrespective of HPV status in head and neck cancers including oral cancer [13].…”
Section: Pd-1/pd-l1 In Oral Cancers and Hpv Infectionsmentioning
confidence: 99%